Respective Influences of Indian Ocean Dipole and El Niño-Southern Oscillation on Indonesian Precipitation - Deni Okta Lestari; Edy Sutriyono; Sabaruddin Sabaruddin; Iskhaq Iskandar (Journal of Mathematical and Fundamental Sciences, 2018)
The respective influences of the Indian Ocean Dipole (IOD) and El Niño-Southern Oscillation (ENSO) on Indonesian precipitation were evaluated using monthly precipitation data from the Global Precipitation Climatology Centre (GPCC) for January 1948 to December 2013. Simultaneous correlation between seasonal precipitation anomalies and climate indices for these two types of climate modes revealed that IOD events have a significant correlation with the precipitation over southern Sumatra, Java, southern Kalimantan, the Nusa Tenggara Islands, some parts of Sulawesi and eastern Papua. Meanwhile, ENSO events have a significant correlation with the precipitation over southern Sumatra, Java, Kalimantan, Sulawesi, and Papua. Droughts during the dry season (JJA and SON) typically occur when a positive IOD event simultaneously occurs with an El Niño event associated with anomalous low SST observed in the Indonesian seas and the southeastern equatorial Indian Ocean. Low SST anomalies lead to low-level wind divergence and reduce water vapor in the lower atmosphere, supress atmospheric convection over the Indonesian region and then cause a decrease in precipitation.